Therapeutic potential of Gynura procumbens in enhancing cytokine regulation in the cervix of rats induced by 7,12-dimethylbenz(a)anthracene: in vivo and in silico investigations - Situmorang, Putri Cahaya; Wibowo, Syahputra; Ilyas, Syafruddin; Nugraha, Sony Eka; Nugraha, Alexander Patera; Utami, Diyah Tri; Nik Abd Rahman, Nik Mohd Afizan; Mukra, Rizal (Elsevier, 2025)
Cytokine dysregulation plays a central role in DMBA-induced cervical inflammation with neoplastic potential. This study investigated the effects of Gynura procumbens (GB) on key cytokines—IL-1β, IL-6, IL-10, and IL-18—using in vivo and in silico approaches. Female rats treated with DMBA received GB extract at 100, 200, or 300 mg/kg weight. GB at 300 mg/kg significantly suppressed IL-1β and IL-18 (p < 0.01) while restoring IL-10 to near-normal levels. IL-6 expression, reduced by DMBA, was upregulated following GB treatment. Histology revealed reduced epithelial damage and improved regeneration. In silico analysis showed that GB's active compounds, particularly nonanedioic and tetradecanoic acids, had higher binding affinity to IL-10 and IL-18 than cisplatin. Molecular dynamics simulations indicated enhanced protein stability, with RMSF values reduced in IL-18 (from 4.7 Å to ∼2.7 Å) and IL-10 (from 6.2 Å to ∼3.1 Å). These results support the anti-inflammatory and immunomodulatory potential of GB for cervical inflammation with neoplastic features.